Research of Mobile Applications Supermarket Based on Smart Pipe Technology - Kunlun Li (Dianxin kexue)
Combining network operators resource advantage, using its unique smart pipe technology, how to build application supermarket on this intelligent network platform was elaborated, a new platform for the mobile application was built, a new business model was proposed.